Urea vs. soybean meal in wintering and finishing rations for beef steers - D. Richardson; E.F. Smith; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1968)
A previous test using sorghum silage (Kans. Agri. Expt. Sta. Bull. 507:5, 1967) indicated that 3 pounds of grain per day in silage would supply enough available energy for reasonably good utilization of nonprotein nitrogen (urea). However, additional grain apparently increased the utilization of urea. This is the second test to obtain information on the minimum amount of readily available energy as grain necessary for efficient utilization of nonprotein nitrogen as a substitute for natural protein. During the wintering phase, the roughage was corn silage with an average of 38.5% dry matter. Grain made up 27% of the dry matter. Prairie hay replaced the silage in the finishing phase. Supplemental treatments are shown in the tables giving the results.
Keywords: Cattlemen& #x27; s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Urea vs. soybean meal; Winter rations; Finishing rations